KUASA, KAPITAL, DAN POLITIK KEBANGSAWANAN PURI AGUNG KARANGASEM DI BALI 2008-2021 - Paramitha, Luh Gede Dana; Erawan, I Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This research aims to find out the capital and power network as the new power base of Puri Agung Karangasem. Social Capital Theory by Pierre Bourdieu is used as analytical tool to find out capital as a power base utilized by the big puri family. Using qualitative methods through interviews, the conclusion of the research results, namely Puri Agung Karangasem naturally has a base of economic capital, cultural capital, symbolic capital, and social capital as part of the rest of the past glory. Of the four capitals, Puri Agung Karangasem utilizes culture in the form of identity and past history and knowledge made by puri Agung Karangasem figures through books on the figures and history of Puri Karangasem which also gives legitimacy to knowledge about culture, as their symbolic power. The symbolic and cultural forces incorporated in their economic and social capital also eventually gave rise to Puri Agung Karangasem.